2004
DOI: 10.1111/j.1365-201x.2004.01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a triple sugar test of colonic permeability in humans

Abstract: Both sucralose and 51Cr-EDTA underwent significant colonic absorption. A significant amount of lactulose also appeared to be absorbed in the colon. This unexpected finding requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 18 publications
2
39
0
2
Order By: Relevance
“…However, it has been postulated that raised intestinal permeability might be involved in the pathogenesis of celiac disease [11] . Andersen et al [12] have shown by a triple sugar test that bowel permeability is increased in ileostomy patients. Perhaps this hyperpermeability could be the triggering factor in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been postulated that raised intestinal permeability might be involved in the pathogenesis of celiac disease [11] . Andersen et al [12] have shown by a triple sugar test that bowel permeability is increased in ileostomy patients. Perhaps this hyperpermeability could be the triggering factor in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…In this literature review, we examine reports of breed associated diversity in GI anatomy 39 and morphology, gastric emptying time (GET), oro-cecal transit time (OCTT), small intestinal transit time 40 (SITT), large intestinal transit time (LITT), intestinal permeability, sodium/potassium fecal concentrations, 41 intestinal flora, and fecal moisture content. Physiological processes 65 -Gastric emptying time (GET) 66 -Oro-cecal transit time (OCTT) 67 -Small intestinal transit time (SITT) 68 -Large intestine transit time (LITT) 69 70 Absorption factors 71 -Fecal moisture content 72 -Electrolyte absorption 73 -Intestinal flora 74 -Intestinal permeability 75 76 77 The lack of published information on the relationship between 78 breed and basal fluid volumes, mucous layer thickness, bile salt 79 composition, and regional pH necessitated its exclusion from this 80 review. 81 The studies described in this review utilized a variety of testing 82 methods.…”
mentioning
confidence: 99%
“…Additional health-beneficiary effects of these dietary carbohydrates include promotion of intestinal calcium absorption and anti-inflammatory effects in the bowel (147). Owing to their small size, these saccharides, when ingested, can slowly penetrate into the circulation by passive intestinal and colonic absorption and can be detected in urine (148,149). As follows from Table 12.6, lactulose is a better ligand for galectins as compared to "standard" lactose, while lactitol and GOS bGal(1 !…”
Section: Other Potential Galectin Binders From Foodmentioning
confidence: 96%